PENGARUH INTELEGENCE QUOTIENT (IQ), EMOTIONAL QUOTIENT (EQ), DAN SPIRITUAL QUOTIENT (SQ) TERHADAP PEMAHAMAN AKUNTANSI SISWA DI SMK SUMPAH PEMUDA 2 - Kusuma, Indra Cahya; Rizki, Lody Mangku (JURNAL AKUNIDA, 2017)
This research is replicated from Rahman (2014) and Pasek (2015). This research aim to examine impact of Intelectual Quotient, Emotional Quotient, and Spritual Quotient to wards Understanding of Accountancy. This study used a survey method that uses primary data collected from questionnaires. The population in this study were student of the Concentration of Accounting at SMK Sumpah Pemuda 2 Ciawi. The member of sample taken in this study are 31 student XII Classi. Hypotesis tets use liniear coreelation and regression. Result of the hypothesis test indicate that Intelectual Quotient, Emitional Quotient, and Spiritual Quotient has positive correlation with understanding of Accountancy. The result showed simulataneous Intelectual Quotient, Emotional Quotient, and Spiritual Quotient has significantly impact toward Understanding of Accountancy. In parcial Intelectual Quotient has a Positive and significant impact towards Understanding of Accountancy, meanwhile Emotional Quotient and Spiritual Quotient has not impact towards Understanding of Accountancy.Key word: Intelectual Quotient (IQ), Emotional Quotient (EQ), Spiritual Quotient (SQ), andÂ Understanding of Accountancy.